Pentachlorophenol exposure in women with gynecological and endocrine dysfunction - Gerhard, Ingrid; Frick, Anita; Monga, Bondo; Runnebaum, Benno (Environmental research, 1999)
Exposure to wood preservatives containing pentachlorophenol (PCP) was detected in 65 women who consulted the Endocrinological Department of the University Hospital of Obstetrics and Gynecology, Heidelberg, Germany, because of gynecological problems. Blood PCP levels ranged from 20.7 to 133 μg per liter of serum. One hundred and six women with similar clinical conditions, corresponding age and body weight, no PCP exposure in history, and PCP levels below 20 μg per liter of serum served as control group. Significant associations were found between serum PCP concentrations, age, and different parameters of the endocrine system. PCP may act centrally on a hypothalamic or suprahypothalamic level which may result in mild ovarian and adrenal insufficiency. PCP may, therefore, play a role in the increasing infertility problem.
Available online 25 May 2002
Gesehen am 18.11.2020